Preliminary results of hematological values for wild population of Spheniscus humboldti in southern Peru - Suarez-Yana, Tania (2018)
The objective of this report was to present data on the hematological profile of the Humboldt penguin (Spheniscus humboldti) in Punta Coles, Peru. Values of hematocrit, white blood cell count and leukocyte formula were determined in four individuals. Blood samples (5 ml) were extracted by jugular puncture. The results were: hematocrit 44.5 ± 4.12%, white blood cell count 17.25 ± 4.57x10³/μl, heterophiles 9.85 ± 1.91x10³/μl, lymphocytes 3.7 ± 0.51x10³/μl, monocytes 1.52 ± 0.99x10³/μl, eosinophils 1.3 ± 0.51x10³/μl. The lymphocytes showed lower values than other wild and captive populations of S. humboldti.